Implementasi Proyek P5 Recycle Sampah Anorganik dalam Membentuk Karakter Disiplin dan Tanggung Jawab pada Siswa Kelas VII SMP Negeri 1 Binjai Hulu - nurul fadilah; Suparno (TANJAK, 2025)
This research aims to describe the implementation of the project of forcing the Pancasila student profile (P5) to recycle inorganic waste in forming discipline and responsibility character in class VII students. This research was motivated by the fact that when students were in the school environment there were still those who violated school rules and regulations. This research uses a qualitative approach and qualitative research methods in descriptive form. The techniques used in this research are observation, interviews and documentation techniques. The results of this research show that the implementation of the project to strengthen the profile of Pancasila students (P5) by recycling inorganic waste in forming discipline and responsibility in class VII students at SMP Negeri 1 Binjai Hulu, has been carried out well and optimally by teachers and students at the school. Teachers' efforts to form a disciplined and responsible character in students through the implementation of the project to strengthen the profile of Pancasila students (P5) by recycling inorganic waste, namely, teaching, modeling, habituation, enforcing rules, guidance, punishment and rewards, supervision and advice. The influencing factors are, habitual factors, family factors, and environmental factors. In order to carry out this implementation, teachers play a full role in forming the character of discipline and responsibility of students at school. It can be concluded that the implementation of the project to strengthen the profile of Pancasila students (P5) by recycling inorganic waste in forming discipline and responsibility in students has been carried out well.